Changes in macronutrient balance during over- and underfeeding assessed by 12-d continuous whole-body calorimetry. - Jebb, SA; Prentice, A; Goldberg, G; Murgatroyd, P; Black, A; Coward, W (1996)
Alterations in energy balance must be accommodated by adjustments in the net storage of the major energy-yielding macronutrients: carbohydrate, protein, and fat. This study used continuous whole-body calorimetry to measure changes in energy expenditure and substrate oxidation during a 12-d imposed energy imbalance in six lean men on mixed diets (overfeeding: 16.5 MJ/d, +33%, n = 3; underfeeding: 3.5 MJ/d, -67%, n = 3). Changes in total energy expenditure (TEE) and its components were modest; TEE changed by +6.2% (overfeeding) and -10.5% (underfeeding). In consequence, body weight changed by +2.90 and -3.18 kg. Marked changes in metabolic fuel selection occurred over the course of the study. Carbohydrate intake (540 and 83 g/d for overfeeding and underfeeding, respectively) exerted direct autoregulatory feedback on carbohydrate oxidation (551 and 106 g/d at day 12 for overfeeding and underfeeding, respectively). Subjects were close to balance by day 5. Changes in protein oxidation were small and not sufficient to prevent the oxidation of body protein mass, or its accretion, in response to energy deficit or surplus. Fat oxidation (59 and 177 g/d for overfeeding and underfeeding, respectively) was not sensitive to dietary fat intake (150 and 20 g/d, for overfeeding and underfeeding, respectively), rather, its oxidation was inversely related to the oxidation of other substrates. Changes in fat balance accounted for 74.1% and 84.0% of the energy imbalance during overfeeding and underfeeding, respectively. This study shows a clear oxidative hierarchy for the macronutrients. Metabolic fuel selection is dominated by the need to maintain carbohydrate balance. This induces inappropriate counterregulatory alterations in fat oxidation during energy surplus.